An effect of side chain length on the solution structure of poly(9,9-dialkylfluorene)s in toluene - Knaapila, M. (2008)
The effect of side chain length of [pi]-conjugated poly(9,9-dialkylfluorene)s has been studied in semi-dilute (10 mg/mL) toluene solutions using small-angle neutron scattering (SANS) and 1H and 2H NMR spectroscopies. Under these conditions, SANS data indicate that poly(9,9-dinonylfluorene) and poly(9,9-dioctylfluorene) are dissolved down to the molecule level and appear as elongated one-dimensional chains (length >20-30 nm). In contrast, the shorter side chain polymers exhibit a self-association so that poly(9,9-diheptylfluorene) forms thin sheet-like (~1 nm) and poly(9,9-dihexylfluorene) thin (~1 nm) and thick sheet-like (>6 nm) aggregates. 1H NMR data, together with the density functional theory (DFT) calculations, however, show that this occurs without changes in the conformation of the polymer backbone.